Fabellae : Frammenti Di Favole Latine e Bilingui Latino-Greche Di Tradizione Diretta (III-IV D. C. ). - Scappaticcio, Maria Chiara. (Untersuchungen Zur Antiken Literatur und Geschichte Series, 2017)
The series consists of a variety of monographs from the fields of Classical Philology and Ancient History. While maintaining a broad thematic and methodological scope, the editors are especially keen on studies showing a thorough and critical engagement with the relevant literary texts and primary sources.